Outdoor Education as an Experiential Learning Approach to Foster Physical Education Interest - Kudus, Ahmad; Muhaimin, Ali; Zainuddin, Fadli; Irmansyah, Johan; Kurniawan, Ari Wibowo (Sportify Journal, 2025)
This study was motivated by the need for innovation in Physical Education, Sports, and Health learning, as some Grade Five students at SDN 05 Danger showed limited enthusiasm and engagement in conventional learning activities. The study aimed to examine the relationship between Outdoor Education implementation and students’ learning interest in physical education at SDN 05 Danger, Masbagik District. This research used a quantitative associative approach with a survey method. The sample consisted of all 42 Grade Five students selected through total sampling. Data were collected using a Likert-scale questionnaire, observation, and documentation, then analyzed through validity testing, reliability testing, simple linear regression, t-test, F-test, and coefficient of determination. The results showed that Outdoor Education had a positive and significant relationship with students’ learning interest, with Y = 4.684 + 0.714X, t = 4.653, p < 0.001, and R² = 0.351.